Phytoremediation: A scientometric analysis of contribution in scielo and scopus databases - Sousa, Ísis Danielle (2021)
The Preservation of soils is a key determinant for human survival. Soil biodiversity influences the quantity and quality of food consumed, so it is a valuable natural resource. However, soil biodiversity is being affected by global man-made changes and currently, after incorrect practices in its use, there are warning signs of soil contamination with diverse pollutants. The hazardous nature of wastes can be mitigated by the application of conventional decontamination methods, such as incineration, composting and landfilling, although such techniques are expansive. A possibility is to consider a viable and promising alternative technique for treatment of contaminated soils by applying biological techniques that have as main objective the stimulation of the growth of the microorganisms using the contaminants as source of energy and food, creating a propitious environment for remediation. It is the case of Phytoremediation, a technique that uses plants and associated soil microbes to decrease the concentration or toxic effects of contaminants in environments, specially in soil. However, it is necessary to know the potential of plant around the world and, Brazil, which holds one of the greatest natural resources and biodiversity on the planet, we lack a ruge knowledge of plants with phytoremediation potential. In the last 20 years, many discussions have been raised, in both academic and business environment, converging to the same consensus: there is a delay in innovations from natural products and derivatives derived from our rich biodiversity. Therefore, this scientometric research bring a broad view of what have been carried in Brazil and abroad concerning phytoremediation studies associated with a critical view about what should be done to boos this research field in order to generate more ecofriendly restoration process to recover polluted lands.